REKONSTRUKSI PENYUSUNAN LAPORAN KEUANGAN BERBASIS TEKNOLOGI PADA BUMDES AMANAH TEMPUREJO - Wulandari, Devi; Yuliarti, Norita Citra; Aspirandi, Rendy Mirwan (Growth, 2023)
Village Owned Enterprises (BUMDes) are business entities established and managed by villages together with local communities to manage village assets, explore village potential and make villages develop for the welfare of village communities, in recording BUMDes financial reports still use a manual system so it is less effective and efficient . Along with the times, the recording of financial statements utilizes technology in the form of the MYOB application which can facilitate the recording of financial reports based on SAK ETAP. The MYOB application is an application from Sage Group products and is a bookkeeping application that functions to make it easier for HR to keep financial records and is the application that has the largest number of users in the world after Quickbooks. Using software will make work more effective and efficient. However, when using this software, the user must be careful and understand because if a slight error occurs, the data processing will repeat from the beginning.